Adaptation of fuel selection to acute decrease in voluntary energy expenditure is governed by dietary macronutrient composition in mice. Issue 18 (23rd September 2021) - Bhandarkar, Nikhil S.; Lahav, Rotem; Maixner, Nitzan; Haim, Yulia; Wong, G. William; Rudich, Assaf; Yoel, Uri
Abstract: In humans, exercise‐induced thermogenesis is a markedly variable component of total energy expenditure, which had been acutely affected worldwide by COVID‐19 pandemic‐related lockdowns. We hypothesized that dietary macronutrient composition may affect metabolic adaptation/fuel selection in response to an acute decrease in voluntary activity. Using mice fed short‐term high‐fat diet (HFD) compared to low‐fat diet (LFD)‐fed mice, we evaluated whole‐body fuel utilization by metabolic cages before and 3 days after omitting a voluntary running wheel in the cage. Short‐term (24–48 h) HFD was sufficient to increase energy intake, fat oxidation, and decrease carbohydrate oxidation. Running wheel omission did not change energy intake, but resulted in a significant 50% decrease in total activity and a ~20% in energy expenditure in the active phase (night‐time), compared to the period with wheel, irrespective of the dietary composition, resulting in significant weight gain. Yet, while in LFD wheel omission significantly decreased active phase fat oxidation, thereby trending to increase respiratory exchange ratio (RER), in HFD it diminished active phase carbohydrate oxidation. In conclusion, acute decrease in voluntary activity resulted in positive energy balance in mice on both diets, and decreased oxidation of the minor energy (macronutrient) fuel source, demonstrating that dietary macronutrient composition determines fuel utilization choices under conditions of acute changes in energetic demand. Abstract : Acute decline in voluntary energy expenditure, as occurred in COVID19‐related lockdowns, results in mice in changes in oxidation fuel selection: Low‐fat fed mice decreased fat oxidation during the active phase of the day; Short‐term high‐fat fed mice decreased carbohydrate oxidation.